Therapeutic status of hydroxychloroquine in COVID-19: A review - Kirandeep Kaur; Sandeep Kaushal; Ishita Gupta Kaushal (Wolters Kluwer Medknow Publications, 2020)
Hydroxychloroquine (HCQ), a 4-aminoquinoline, is used worldwide mainly for its role in management of malaria and rheumatoid arthritis. In the present pandemic of coronavirus disease (COVID)-2019, the drug is being repurposed, based on its in vitro evidence of efficacy against coronavirus. There has been a lot of information, for and against the drug, and this review is an effort to bring forth the evidence and current understanding regarding role of HCQ in COVID-19. Clinical studies, case reports, and in vitro studies have generated conflicting results. There are concerns for use of HCQ because of the variable results and the known adverse effects like QT prolongation and hypoglycemia. In the current scenario, recommendations from Indian Council of Medical Research for use of HCQ in the prophylaxis of COVID-19 are being followed.